Phenotypic and molecular characterisation of clinical carbapenem-resistant acinetobacter baumannii / Kong Boon Hong - Kong, Boon Hong (2012)
Acinetobacter baumannii is an opportunistic pathogen with increasing relevance in nosocomial infections. They cause a wide range of clinical complications, such as pneumonia, septicemia, urinary tract infection, wound infection, and meningitis, particularly in immunocompromised patients. Treatment of A. baumannii infections is often complicated by their resistance to multiple antimicrobial agents available.Carbapenem has remained as the effective antimicrobial agent for the treatment of A. baumannii infections. However, carbapenem-resistant A. baumannii is increasingly reported worldwide. In Malaysia, detailed information on the epidemiology and the mechanism of antimicrobial resistance of A. baumannii is still lacking. Hence, the objectives of this study were to investigate the prevalence of antimicrobial resistance,mechanisms of carbapenem resistance among the A. baumannii isolates and to provide sound scientific evidence of epidemiologic spread of A. baumannii in the hospital setting. In 2006-2009, a total of 189 A. baumannii isolates wereisolated from patients(n=171), environment (n=9) and hands of healthcare workers (HCWs) (n=9) in intensive care unit, University Malaya Medical Centre. One-hundred and eighty-five isolates (170 clinical; 7 environmental; 8 HCWs) were identified as A. baumannii by amplified ribosomal DNA restriction analysis (ARDRA). All the clinical, 7 environmental and 1 HCW A. baumannii isolates were multidrug-resistant to at least 3 groups of antimicrobial agents, with high resistance rates to the aminoglycoside, penicillin, cephalosporin, quinolone, carbapenem and foliate inhibitor. All the 2006 isolates appeared susceptible to cefoperazone/sulbactam. However, resistant isolates were detected in 2007 to 2009 isolates. Polymyxin B has remains effective against the A. baumannii isolates. None of the 175 carbapenem-resistant isolates was metallo-β-lactamase (MBL) iii producers based on phenotypic screening and PCR detection of the MBL genes. blaOXA- 51 gene which is intrinsic to A. baumannii was present in all the isolates and ISAba1- blaOXA-23 gene was detected in 174 isolates. Resistance to imipenem was mainly due to overexpression of the OXA-23 induced by the promoter sequences located in insertion element, ISAba1 upstream of the blaOXA-23 gene. Polymerase chain reaction detection of integrons showed class 1 integrons were predominant among the 185 isolates, with 17 isolates were also harbouring class 2 integrons. The integron gene cassettes contained the most number of resistance determinants to aminoglycosides (aadB, aadA, aadDA1, aacC1 and aacA4). There was no correlation between the blaOXA-23 gene and integrons, suggesting that integrons were unlikely involved in the mobility of blaOXA-23 gene in the A. baumannii isolates. Of the 175 carbapenem-resistant isolates, 164 (93.7%) isolates harboured 1-15 plasmids each, ranging from 1.6 kb to 125.1 kb. A total of 98 plasmid profiles were defined, with P49 (44.8 kb, 21.6 kb, 6.8 kb), P52 (44.8 kb, 6.8 kb) and P53 (44.8 kb, 16.1 kb, 6.8 kb) the predominant plasmid profiles, harbouring the common plasmids, 6.8 kb and 44.8 kb. Southern hybridisation analyses revealed that blaOXA-23 gene was dispersed on diverse locations on the plasmids and chromosome among multiples isolates. However, the blaOXA-23 gene was not transferable. To our knowledge, this is the first report of the plasmid- and chromosomal-mediated OXA-23-producing carbapenem-resistant A. baumannii in Malaysia. PFGE and REP-PCR typing had successfully discriminated all the A. baumannii isolates. The non-multidrug-resistant had high genetic variability and were distinct from the multidrug-resistant isolates. However, the carbapenem-susceptible isolates could not be distinguished from the carbapenem-resistant isolates by both typing methods. The OXA-23-producing clinical, environmental and HCW isolates shared similar resistance phenotype and had closely related PFGE and REP-PCR profiles, indicating a possible iv transmission route may occur between the environment, HCW and patients. OXA-23- producing A. baumannii isolates were observed in the ICU area throughout 2006-2009,indicating the endemicity of the isolates. In addition, an occurrence of new A. baumannii clone was observed in 2009 based on PFGE analysis.In conclusion, the dissemination of the carbapenem-resistant A. baumannii within the ICU, UMMC from 2006-2009 was of OXA-23-producing isolates. PFGE and REPPCR molecular typing were useful in discriminating the nosocomial related A. baumannii isolates. A. baumannii is able to obtain resistance genes, thus could confront the extensive exposure to antimicrobial agents and persisted in the ICU. Therefore, evaluation of effective antimicrobials and infection control measures are important to control the dissemination of carbapenem-resistant A. baumannii isolates within the hospital.